1988
DOI: 10.1038/335088a0
|View full text |Cite
|
Sign up to set email alerts
|

The proto-oncogene c-kit encoding a transmembrane tyrosine kinase receptor maps to the mouse W locus

Abstract: Mice carrying mutations at the W locus located on chromosome 5 are characterized by severe macrocytic anaemia, lack of hair pigmentation and sterility. Mutations at this locus appear to affect the proliferation and/or migration of cells during early embryogenesis and result in an intrinsic defect in the haematopoietic stem cell hierarchy. An understanding of the molecular basis of the complex and pleiotropic phenotype in W mutant mice would thus provide insights into the important developmental processes of ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
519
2
9

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,265 publications
(537 citation statements)
references
References 12 publications
7
519
2
9
Order By: Relevance
“…The involvement of cochlear melanocytes in generating the endocochlear potential was recognized later in a studies with “viable dominant spotting” mouse mutants, with a mutation in the W locus (Steel et al, 1987; Steel and Barkway, 1989). Shortly hereafter, Kit was found to be the gene product of the W locus (Chabot et al, 1988; Geissler et al, 1988), and it was shown to primarily affect the survival of migratory melanoblasts (Cable et al, 1995). In humans, KIT mutations can result in the neurocristopathy (a pathology affecting normal neural crest development) piebaldism [MIM 172800], a disorder characterized by areas of skin and hair devoid of melanocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of cochlear melanocytes in generating the endocochlear potential was recognized later in a studies with “viable dominant spotting” mouse mutants, with a mutation in the W locus (Steel et al, 1987; Steel and Barkway, 1989). Shortly hereafter, Kit was found to be the gene product of the W locus (Chabot et al, 1988; Geissler et al, 1988), and it was shown to primarily affect the survival of migratory melanoblasts (Cable et al, 1995). In humans, KIT mutations can result in the neurocristopathy (a pathology affecting normal neural crest development) piebaldism [MIM 172800], a disorder characterized by areas of skin and hair devoid of melanocytes.…”
Section: Discussionmentioning
confidence: 99%
“…We used W mutant mice as recipients for transplantation to examine whether transduced SSCs could restore the spermatogenesis of the recipient mouse that was congenitally infertile and lack endogenous spermatogenesis due to mutations in the c-Kit receptor tyrosine kinase gene. W mice were also chosen as it has been previously shown that efficient colonization by transplanted SSCs was enhanced in the W testis environment (Chabot et al, 1988;Geissler et al, 1988;Shinohara et al, 2001). Therefore, the presence of spermatogenesis inside the testes of W mice could only be derived from the transplanted donor SSCs.…”
Section: Lentiviral Transduction Of Mouse Sscsmentioning
confidence: 99%
“…CD117 (also known as c-kit) is a type-III tyrosine kinase receptor with five extracellular, immunoglobulin-like domains. This protein is strongly involved in myelopoiesis, melanogenesis and spermatogenesis (Yarden et al, 1987;Chabot et al, 1988). In some cancers such as gastro intestinal stromal tumours (GISTs), point mutations lead to abnormal expression and constitutive activity of the receptor.…”
mentioning
confidence: 99%